INVESTIGATION OF RELIGIOUS MODERATION VALUES IN GROWING TOLERANT BEHAVIOR IN STUDENTS THROUGH THE STORY OF WALISONGO : INVESTIGATION OF RELIGIOUS MODERATION VALUES IN GROWING TOLERANT BEHAVIOR IN STUDENTS THROUGH THE STORY OF WALISONGO - Aminatun; Widodo algani (CV. Doki Course and Training, 2023)
Islam encourages its followers to behave tawasuth, meaning in the middle or balanced, not extreme, and not inclusive. NaturetawasuthThis is part of religious moderation that should be instilled in students so that students have a moderate attitude in the life of the nation and state. In the midst of the plurality of the Indonesian nation, religious moderation is absolutely necessary and taught to the students in order to become human beings who are conciliatory, full of love and tolerant in the future. The involvement of religious teachers in providing an understanding of nature tawasuth for students, it needs to be cultivated and echoed. The content of Islamic religious education material emphasizes understanding compassion, loving each other, respecting each other, and helping each other in goodness. Because with this understanding, students can implement it in students' daily lives. The article discusses the role of religious teachers in instilling religious moderation.